CONNECTOR: a geolocated mobile social service - Almeida, Pedro
The widespread and availability of increasingly powerful mobile devices is contributing for the incorporation of new services and features on our daily communications and social relationships. In this context, geolocation of users and points of interest in mobile devices may contribute, in a natural way, to support either the mediation of remote conversations as the promotion of face-to-face meetings between users, leveraging social networks. The CONNECTOR system is based on geolocation data (people, contente and activities), enabling users to create and develop their personal relations with other members of the CONNECTOR social network. Users, maps, sharing features and multimedia content are actors in this social network allowing CONNECTOR to address the promotion of geolocated social networks driven by physical proximity and common interests among users. This chapter discusses the work undertaken for the conceptualization and development of the CONNECTOR system. Preliminary evaluation results along with usage contexts are also presented. The chapter concludes with a discussion about future developments in geolocation and personalization in mobile communication services.